The Current Role of Adjuvant Chemotherapy in Locally Advanced Nasopharyngeal Carcinoma - Su, Lin; She, Lei; Shen, Liangfang (Frontiers in Oncology, 2021)
Nasopharyngeal carcinoma (NPC) is one of the most common malignant tumors of the head and neck, and originates from the mucous epithelium of the nasopharynx. Because it is ‘hidden’, the symptoms of NPC can easily be missed, and more than 70% of patients present with locally advanced disease at diagnosis. Concurrent radiation therapy with chemotherapy can significantly improve regional control of NPC. At present, distant metastasis is the main cause of treatment failure. At the end of the 20th century, clinical trial No. IG0099 in the United States confirmed the effectiveness of adjuvant chemotherapy (AC) for the first time. However, in the past 20 years, various clinical trials and meta-analyses conducted globally have yielded contradictory results regarding the effect of AC on locally advanced NPC. AC has changed from category 1 to the current category 2A in the National Comprehensive Cancer Network (NCCN) guidelines, and it remains controversial whether AC can significantly improve the survival of NPC patients. Here, we comprehensively analyzed the role of AC in locally advanced NPC by comparing some treatment methods. We conclude the role of AC in treating locally advanced NPC, based on the studies presented remains undefined but is associated with increased toxicity.